2021
DOI: 10.21037/atm-21-6458
|View full text |Cite
|
Sign up to set email alerts
|

A deep convolutional neural network-based method for laryngeal squamous cell carcinoma diagnosis

Abstract: Background: Laryngeal squamous cell carcinoma (LSCC) is one of the most common tumors of the respiratory tract. Currently, the diagnosis of LSCC is mainly based on a laryngoscopy analysis and pathological findings. Deep-learning algorithms have been shown to provide accurate clinical diagnoses. Methods: We developed a deep convolutional neural network (CNN) model, and evaluated its application to narrow-band imaging (NBI) endoscopy and pathological diagnoses of LSCC at several hospitals. A total of 4,591 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…The algorithm used was Inception V3 and AUC was 0.994 for the validation dataset and 0.981 for the testing dataset. 23 …”
Section: Resultsmentioning
confidence: 99%
“…The algorithm used was Inception V3 and AUC was 0.994 for the validation dataset and 0.981 for the testing dataset. 23 …”
Section: Resultsmentioning
confidence: 99%
“…By extracting several images per patient, we increased our dataset to a total of 1448 images. These numbers are in vast contrast with some exceptional databases from recent studies 25,26,28–30 . We, therefore, used the dataset collected by Yin et al to increase the number of data 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Only in recent years has there been a constant rise in publications of articles investigating the application of AI in laryngoscopic images. Although we did not performed a systematic review of literature, a thorough literature search revealed over 15 publications in the last 6 years 16–32 . A rough summary of these articles showed that all but one research group investigated still images (i.e., photos) of laryngeal lesions in a postprocessing method.…”
Section: Introductionmentioning
confidence: 99%
“…In this field, He et al ( 9 ) applied CNN to interpret images of laryngeal squamous cell carcinoma using static NBI frames to determine whether a lesion was benign or malignant. The model reached an accuracy of 90.6%, a sensitivity of 88.8%, and a specificity of 92.2%.…”
Section: Aims Of Videomicsmentioning
confidence: 99%